SISTEM INSTALASI PENGOLAHAN AIR-LIMBAH (IPAL) KOMUNAL DI RW 11 KELURAHAN KERTAJAYA KECAMATAN GUBENG SURABAYA - Aditya Wijaya; Didik Sugeng Purwanto; Suprijandani . (Poltekkes Kemenkes Surabaya, 2014)
Urban sanitation remained a difficult problem to overcome, particularly waste watermanagement. Improper wastewater discharges that do not meet health and environmentalrequirements maybe harmful to health. In order to control discharges of domestic wastewater,the Governor of East Java issued Regulation No. 72 of 2013 regarding Wastewater Standard forIndustries and/or Other BusinessActivities that includes parameters such as pH, BOD,COD,TSS,Oils and Fats. The purpose of the present study was to determine the system and processesofcommunal WWTP in RT 4 RW 11 on Jalan Kertajaya IV Raya Kelurahan Kertajaya KecamatanGubeng of Surabaya Municipality.This was a descriptive and cross-sectionalstudy. Data were collected through observations,measurements, interviews, laboratory tests, as well as secondary data collection. Water sampleswere taken three times at the inlet and outlet of the WWTP. The collected data weresubsequently analyzed in descriptive manner.Results showed that the inflow was greater than the outflow, leading to overflow of theWWTP. Sources of wastewater conslsted of domestic wastewater, water used to wash utilities,water discharge from motor vehides washing activities. Wastewater was treated by biologicalmethod consisted of an anaerobic system and physical methods involving a filtration system.Wastewater was sampled at the inlet and outlet points of the WWTP using a time-combinationmethod. BOD removal efficiency was found to be 29.9%-67.9%; COD removal efficiency was8.5%-44.6%; TSS removal efficiency was 41.7%-92.3%; Oil and Fat removal efficiency was 5%-61.9%. The quality of treated domestic wastewater of RW 11 Kelurahan Kertajaya did not meetthe deSignated requirements with regard to parameters of BOD,COD,Oil and Fat.It is recomended to improve the processing capacity of the WWTP in order to preventoverflows, increase the dimension of the biological treatment facility, and add a grease trap unitto help the effluent quality to meet the standards stated in EastJava Governor Regulation No. 72of 2013